2021
DOI: 10.1155/2021/9969032
|View full text |Cite
|
Sign up to set email alerts
|

Lightning Protection Improvement and Economic Evaluation of Thailand’s 24 kV Distribution Line Based on Difference in Grounding Distance of Overhead Ground Wire

Abstract: This study determines the voltage across insulators after a direct lightning strike to an overhead ground wire on a 24 kV pole structure for different grounding distances of overhead ground wire, to calculate the maximum ground resistance required to avoid disruption of the distribution line system using ATP-EMTP software. The results show that when a 40 kA lightning current, the average lightning current in Thailand, strikes a 24 kV pole structure, the maximum ground resistance should not exceed 4 Ω for a 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…The literature reveals that for distribution system of voltage less than 1000 volts the grounding resistance should be less than 4 Ω to safely discharge the energy from lighting impulses (Sestasombut & Ngaopitakkul, 2021) and most of the standards (International Electrotechnical Commission., 2010a) and (BIS, 2006) recommend ground resistance of less than 5 Ω. The impacts of lightning depends upon the type of lightning waveform, type of materials used in electrical installation and topographical features of the area (Sestasombut & Ngaopitakkul, 2021). The effect of lightning on concrete buildings considering risk to human life by (Kasza & Kovacs, 2019) showed that both direct and indirect lightning waves have impact on the human life as well as loss of economy.…”
Section: Introductionmentioning
confidence: 99%
“…The literature reveals that for distribution system of voltage less than 1000 volts the grounding resistance should be less than 4 Ω to safely discharge the energy from lighting impulses (Sestasombut & Ngaopitakkul, 2021) and most of the standards (International Electrotechnical Commission., 2010a) and (BIS, 2006) recommend ground resistance of less than 5 Ω. The impacts of lightning depends upon the type of lightning waveform, type of materials used in electrical installation and topographical features of the area (Sestasombut & Ngaopitakkul, 2021). The effect of lightning on concrete buildings considering risk to human life by (Kasza & Kovacs, 2019) showed that both direct and indirect lightning waves have impact on the human life as well as loss of economy.…”
Section: Introductionmentioning
confidence: 99%